2006
DOI: 10.1093/jb/mvj181
|View full text |Cite
|
Sign up to set email alerts
|

Raised Serum Chondroitin Sulfate Epitope Level in Ovarian Epithelial Cancer

Abstract: These results reflect changes in ECM metabolism in progressive ovarian cancer, which cause an increase in serum CS epitopes and HA. Therefore, serum CS epitopes may provide useful biomarkers for cancers and other disorders of the ovary. Measurement of serum HA provided complementary information, which may be useful as a discriminator between benign ovarian disorders and malignant ovarian diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…Studies of experimental canine osteoarthritis cartilage revealed that early in diseases there were distinctive changes in the CS epitopes long before there was any cartilage destruction (20). Changes in the sulfation of CS were also reported in the PG fragments found in synovial fluid following joint trauma (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of experimental canine osteoarthritis cartilage revealed that early in diseases there were distinctive changes in the CS epitopes long before there was any cartilage destruction (20). Changes in the sulfation of CS were also reported in the PG fragments found in synovial fluid following joint trauma (21).…”
mentioning
confidence: 99%
“…It is reactive with shark CS-PGs, and the epitope was also detected in commercial CS preparations (CS-C and CS-D) from shark cartilage, but the antibody is unreactive with other glycosaminoglycans (GAGs) (25). An enzyme-linked immunosorbent assay (ELISA) has shown that this mAb detected an increased level of WF6 epitope in serum samples from patients of osteoarthritis and rheumatoid arthritis (19) and in those of ovarian cancer (20). The established specificity of the antibody and its restricted distribution among CS chains has suggested that the epitope is a specific sequence found in some but not all CS chains and is composed of sulfated disaccharides, including A unit (GlcUA␤1-3GalNAc(4-O-sulfate)), C unit (GlcUA␤1-3GalNAc(6-O-sulfate)), and D unit (GlcUA(2-O-sulfate)␤1-3GalNAc(6-O-sulfate)).…”
mentioning
confidence: 99%
“…Chondroitin sulfate as part of the tumor microenvironment accumulates in the stromal compartment of many solid tumors, including breast tumors (Olsen et al, 1988;Kovalszky et al, 1990;Alini and Losa, 1991;Ricciardelli et al, 1997Ricciardelli et al, , 1999Ricciardelli et al, , 2009Vijayagopal et al, 1998;Suwiwat et al, 2004;Pothacharoen et al, 2006;Sakko et al, 2008;Teng et al, 2008;Kalathas et al, 2009), the functional relevance of which had not been analyzed so far. Here, we utilized intra-tumor injections of ChABC in an orthotopic mouse model to demonstrate that enzymatic elimination of endogenous breast cancer-associated chondroitin sulfate leads to an increased metastatic burden.…”
Section: Discussionmentioning
confidence: 99%
“…Several laboratories have also begun to elucidate potential roles for chondroitin sulfates and CSPGs in tumor biology. Strikingly increased levels of chondroitin sulfates and CSPGs have been observed in the microenvironment of a number of human solid tumors, including melanoma, ovarian adenocarcinomas, hepatocarcinoma, prostate tumors, colon adenocarcinoma, and breast cancer (Olsen et al, 1988;Kovalszky et al, 1990;Alini and Losa, 1991;Ricciardelli et al, 1997Ricciardelli et al, , 1999Ricciardelli et al, , 2009Vijayagopal et al, 1998;Suwiwat et al, 2004;Pothacharoen et al, 2006;Sakko et al, 2008;Teng et al, 2008;Kalathas et al, 2009). The functional significance of this observation for cancer progression is unknown, but increased deposition of chondroitin sulfates within malignant tissues raises the possibility of a cancer therapy targeted towards tumor-associated chondroitin sulfates.…”
Section: Introductionmentioning
confidence: 99%
“…Monoclonal antibodies (mAbs) that recognize specific features of the repeating disaccharide region of CS chains have been generated, and epitopes of some of them have been characterized [12][13][14][15][16]. Studies using anti-CS mAbs have revealed restricted spatiotemporal patterns of the expression of specific CS structures in various tissues during growth and development, and in pathological conditions [16][17][18][19]. However, so far, no antibodies have been reported which recognize the GAG-protein linkage region.…”
Section: Introductionmentioning
confidence: 99%